The Effectiveness of Digital Health Interventions in the Multidisciplinary Management of Diabetes: Implications for Physicians, Nurses, Dentists, and Radiologists (The Review of Diabetic Studies, 2024)
Background: Diabetes mellitus is a complex chronic disease requiring multidisciplinary care from physicians, nurses, dentists, and radiologists. Digital health interventions, including mobile health applications, telemedicine, and remote monitoring, are increasingly used to enhance diabetes management. Despite the proliferation of these technologies, evidence regarding their effectiveness across different healthcare professional roles remains scattered.Objective: This systematic review aimed to evaluate the effectiveness of digital health interventions in the multidisciplinary management of diabetes and to identify implications for clinical practice among physicians, nurses, dentists, and radiologists.Methods: A systematic search was conducted across multiple databases, including PubMed, Scopus, and Web of Science, following the PRISMA guidelines. The initial search yielded 962 articles published between 2000 and 2025. After removing duplicates and screening titles, abstracts, and full texts based on inclusion and exclusion criteria, 19 studies were included in the final review. Eligible studies examined digital health interventions for adults with type 1 or type 2 diabetes, addressing outcomes such as glycemic control, patient adherence, lifestyle modification, and interprofessional collaboration. Data extraction focused on intervention type, target professional role, outcomes, and implementation factors. Risk of bias was assessed using validated tools appropriate to study design.Results: The included studies demonstrated that digital health interventions significantly improved glycemic control, medication adherence, and patient engagement. Interventions facilitating interprofessional collaboration enhanced care coordination and monitoring of diabetes-related complications. Nurses and physicians benefited most from telehealth platforms, while dental professionals leveraged digital tools for oral health monitoring, and radiologists for imaging-based complication surveillance.Conclusion: Digital health interventions are effective in supporting multidisciplinary diabetes management. Integrating these technologies into routine practice can improve clinical outcomes, patient self-management, and professional collaboration. Future research should focus on long-term implementation strategies and the equitable distribution of digital health resources across healthcare settings.